2015
DOI: 10.1136/sextrans-2015-052270.388
|View full text |Cite
|
Sign up to set email alerts
|

P09.04 Trichomonas vaginalisandmycoplasma genitalium: age-specific prevalence and disease burden in men attending a sexually transmitted infections clinic in amsterdam, the netherlands

Abstract: Abstracts A148Sex Transm Infect 2015;91(Suppl 2):A1-A258

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
3
9
1
Order By: Relevance
“…gonorrhoeae screening. This prevalence was not significantly different from the 3.1 and 4.5% M. genitalium prevalence reported in the Netherlands [5,6] but was slightly lower than the 4.9% prevalence reported in Denmark [11]. This percentage makes M. genitalium the second most prevalent sexually transmitted microorganism after C. trachomatis, as was previously reported in other European studies [5,6,22].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…gonorrhoeae screening. This prevalence was not significantly different from the 3.1 and 4.5% M. genitalium prevalence reported in the Netherlands [5,6] but was slightly lower than the 4.9% prevalence reported in Denmark [11]. This percentage makes M. genitalium the second most prevalent sexually transmitted microorganism after C. trachomatis, as was previously reported in other European studies [5,6,22].…”
Section: Discussionsupporting
confidence: 62%
“…However, the African and American continents are much more affected than Europe, with 42.8 million and 57.8 million adults infected in Africa and America, respectively, versus only 14.3 million adults infected in Europe in 2008 [3]. In Europe, the prevalence of T. vaginalis infection was recently evaluated to be between 0.5 and 1.4% in patients visiting general practitioners and STI clinics in the Netherlands [5,6], but additional European prevalence data are needed. The prevalence of M. genitalium infection ranges from 1 to 3% in the general population worldwide and rises to 38% in African sex workers and STI testing centres [7e9].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of M. genitalium has earlier been reported to range between 2% and 6% in theNetherlands depending on the population tested. 1517 The difference in M. genitalium prevalence found in the present study is probably due to a general increase in time of the prevalence of M. genitalium in the Dutch population and to extensive inclusion of anal specimens in the present study. The superior sensitivity of the TMA-based Aptima assays that we used compared to in-house PCR assays could also play a role in the differences found.…”
Section: Discussionmentioning
confidence: 50%
“…In the Netherlands, prevalence of M. genitalium has previously been reported to range between 2% and 6%. 1517 Dutch guidelines do not recommend routine testing in symptomatic patients and only advise to consider testing men with a persistent non-gonococcal urethritis (NGU). 18 They promote a conservative approach with regard to M. genitalium screening and treatment for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…We found only two infections with TV in the study population, which corresponds with low prevalence also found in other comparable studies on TV in MSM. A low prevalence in MSM may be due to a general higher persistence of this pathogen in the female urogenital tract [61][62][63]. On basis of the study results, the inclusion of TV in a regular STI testing scheme for MSM is not recommend.…”
Section: Sti Prevalencesmentioning
confidence: 86%